2017
DOI: 10.1161/circresaha.116.310277
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Tissue Engineering With Cells Derived From Human-Induced Pluripotent Stem Cells and a Native-Like, High-Resolution, 3-Dimensionally Printed Scaffold

Abstract: Rationale Conventional three-dimensional (3D) printing techniques cannot produce structures of the size at which individual cells interact. Objective Here, we used multiphoton-excited, 3-dimensional printing (MPE-3DP) to generate a native-like, extracellular matrix (ECM) scaffold with submicron resolution, and then seeded the scaffold with cardiomyocytes (CMs), smooth-muscle cells (SMCs), and endothelial cells (ECs) that had been differentiated from human induced-pluripotent stem cells (iPSCs) to generate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
218
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(222 citation statements)
references
References 26 publications
1
218
1
2
Order By: Relevance
“…Compared with the other engineering approaches such as solid substrate seeding [2123] or hydrogel molding [20,24], 3D bioprinting strategy has inherent advantages in fabricating a highly organized cardiac structure. Although several studies have reported cardiac tissue engineering and bioprinting in the past several years [2528], the cardiac constructs reported in past were small scale with low-level tissue maturation and disoriented muscle fibers, resulting in weak contractility. Therefore, we utilized 3D bioprinting principle to fabricate uniformly organized, centimeter-scaled cardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the other engineering approaches such as solid substrate seeding [2123] or hydrogel molding [20,24], 3D bioprinting strategy has inherent advantages in fabricating a highly organized cardiac structure. Although several studies have reported cardiac tissue engineering and bioprinting in the past several years [2528], the cardiac constructs reported in past were small scale with low-level tissue maturation and disoriented muscle fibers, resulting in weak contractility. Therefore, we utilized 3D bioprinting principle to fabricate uniformly organized, centimeter-scaled cardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nakatana et al have recently engineered a large tissue construct consisting of cardiomyocytes, endothelial cells and vascular cells which were derived from human iPSCs [453]. Likewise, human ESCs and iPSCs have been utilized for the development of 3-dimesional microtissues formed by SC-derived cardiovascular cells [454,455]. In order to mimick human sized organs, specialized scaffolds are needed that provide characteristics similar to the cardiac ECM, match the strength of native myocardium and allow re-population with cardiac cells.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Differentiation protocols have been published for CMs, FBs, endothelial, and epicardial cells. Therefore, iPSCs now offer the opportunity to produce all the essential cellular components of the cardiovascular system in vitro [98]. IPSCs can be directly generated from the reversal conversion (reprogramming) of adult mature cells (FBs, keratinocytes, peripheral blood cells, or renal epithelial cells) via retroviral transduction of stemness transduction factors, such as Oct 3/4, Klf4, Sox2 and c-Myc, as well as using chemicals and reprogramming proteins [99,100].…”
Section: D Bioprinting Of the Cardiovascular Systemmentioning
confidence: 99%
“…Additionally, multiphoton-excited 3D printing was used to generate a native-like extracellular matrix scaffold with submicron resolution, and was able to achieve the individual cell interaction [98]. CMs, smooth muscle cells, and ECs were differentiated from human iPSCs to fabricate the cardiac patch.…”
Section: Regeneration and Pharmacological Study Of 3d Bioprintedcardimentioning
confidence: 99%